Superalloys : alloying and performance - Geddes, Blaine (ASM International, 2010)
"This practical guide provides an introduction for understanding the compositional complexity of superalloys superalloy and the wide range of alloys developed for specific applications. The basics of alloying, strengthening mechanisms, and structure of superalloys are explained in optimizing particular mechanical properties, oxidation/corrosion resistance, and manufacturing characteristics such as castability, forgeability, and weldability."--Publisher's description
Keywords: Alloys.; elektronické knihy; electronic books